Current trends in the German language and their reflection in the training of specialists in higher education institutions: research activities of the department of German linguistics - Kotovskaya, Svetlana S. (Journal of the Belarusian State University. Philology, 2024)
Some current problems in the development of the German language, concerning its grammatical structure and lexical composition are considered. The functional features of the analysed language units, methods of their translation into Russian and Belarusian languages are described. The results of a study of forms of gender correctness expression in German language, international vocabulary, abbreviations, tag-question are presented. The role of the results obtained for the training of specialists in German philology is outlined. The contribution to the development of this scientific problem by the staff, master degree students and students of the department of German linguistics of the faculty of philology of the Belarusian State University as well as the prospects of its research are defined.
Keywords: German language; Belarusian language; international vocabulary; abbreviations; tag-question; pragmatics; translation; gender correctness